ANTIISCHEMIC THERAPY IN TREATING CHRONIC CORONARY SYNDROME - Pandrc, Milena; Kostovski , Vanja (Srpski medicinski časopis Lekarske komore, 2025)
Myocardial ischemia is pathophysiologically based on the inadequate balance between the supply of oxygenated blood and the myocardial oxygen demand. Clinically, it presents as anginal pain with a typical localization, nature, intensity, and accompanying symptoms, primarily exercise intolerance. The diagnostic algorithm includes clinical examination, non-invasive and invasive diagnostic procedures, with coronary angiography as the gold standard. Conservative treatment of stable angina pectoris, in addition to lifestyle modification and elimination of traditional risk factors, involves the use of novel medications, including ranolazine, which stands out for its unique mechanism of action, effectiveness, and safety. Ranolazine is effective in reducing manifestations of ischemia and angina, with a potential effect on left ventricular dysfunction – primarily diastolic and electrical instability.
Keywords: myocardial ischemia; conservative treatment of angina pectoris; ranolazine